The Verticillium‐specific protein VdSCP7 localizes to the plant nucleus and modulates immunity to fungal infections. Issue 1 (13th April 2017) - Zhang, Lisha; Ni, Hao; Du, Xuan; Wang, Sheng; Ma, Xiao‐Wei; Nürnberger, Thorsten; Guo, Hui‐Shan; Hua, Chenlei
Summary: Fungal pathogens secrete effector proteins to suppress plant basal defense for successful colonization. Resistant plants, however, can recognize effectors by cognate R proteins to induce effector‐triggered immunity (ETI). By analyzing secretomes of the vascular fungal pathogen Verticillium dahliae, we identified a novel secreted protein VdSCP7 that targets the plant nucleus. The green fluorescent protein (GFP)‐tagged VdSCP7 gene with either a mutated nuclear localization signal motif or with additional nuclear export signal was transiently expressed in Nicotiana benthamiana, and investigated for induction of plant immunity. The role of VdSCP7 in V. dahliae pathogenicity was characterized by gene knockout and complementation, and GFP labeling. Expression of the VdSCP7 gene in N. benthamiana activated both salicylic acid and jasmonate signaling, and altered the plant's susceptibility to the pathogens Botrytis cinerea and Phytophthora capsici . The immune response activated by VdSCP7 was highly dependent on its initial extracellular secretion and subsequent nuclear localization in plants. Knockout of the VdSCP7 gene significantly enhanced V. dahliae aggressiveness on cotton. GFP‐labeled VdSCP7 is secreted by V. dahliae and accumulates in the plant nucleus. We conclude that VdSCP7 is a novel effector protein that targets the host nucleus to modulate plant immunity, and suggest that plants can recognize VdSCP7 to activate ETI during fungal infection.